Faktor Risiko Infeksi Soil Transmitted Helminth pada Perajin Batu Bata di Provinsi Jawa Tengah - Lilik Setyowatiningsih; Bambang Heru Budianto; Muhammad Samsi (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
Worm infections are one of health problem in developing countries. The most infected worm parasite is the Soil-Transmitted Helminth group. The worm infected disease is generally associated with socioeconomic factors as well as clean and healthy living behaviour. Humans can be infected after ingesting food contaminated by worm eggs for A. lumbricoides and T. trichiura or through skin penetration by hookworm infective larvae. The work type of brick making is closely related to STH infection because related to the soil as the main raw material of bricks. This study aims to determine the level of infection intensity, infection risk factors, and the main risk factors of STH infection in the brick maker in Central Java Province. This research is observational research using a cross-sectional design. The results of this study indicate that the degree of intensity of STH infection in brick maker in Central Java Province is categorized in mild infections with STH infecting worms, including Ascaris lumbricoides, Trichuris trichiura, Hookworm and mixed infection (Ascaris and Trichuris). Risk factors associated with STH infection in brick craftsmen in Central Java Province were knowledge of STH (OR: 4.7 in 95% CI 1.2 - 17.5; p = 0.022) and environmental Sanitation (OR: 7, 3 95% CI 1.9 - 27.5; p = 0.002). The main risk factor that has the most influence on STH infection in brick craftsman in Central Java Province is environmental sanitation (OR: 5,7 95% CI 1,5 - 22,0; p: 0,012).